2017
DOI: 10.1016/j.celrep.2017.10.102
|View full text |Cite
|
Sign up to set email alerts
|

Niche Cadherins Control the Quiescence-to-Activation Transition in Muscle Stem Cells

Abstract: SUMMARY Many adult stem cells display prolonged quiescence, promoted by cues from their niche. Upon tissue damage, a coordinated transition to the activated state is required, as non-physiological breaks in quiescence often lead to stem cell depletion and impaired regeneration. Here, we identify cadherin-mediated adhesion and signaling between muscle stem cells (satellite cells; SCs) and their myofiber niche as a mechanism that orchestrates the quiescence-to-activation transition. Conditional removal of N-cadh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
128
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 67 publications
5
128
0
1
Order By: Relevance
“…The basal surface of satellite cells attaches to the basal lamina and the apical surface to the myofiber. M-cadherin, a well-known satellite cell marker, and its partner b-catenin are localized on the apical surface and form cell-cell adherence junctions with the myofiber (Goel et al, 2017;Irintchev et al, 1994). Pard3, a member of the Par complex, is localized along the apical surface of satellite cells (Dumont et al, 2015b;Troy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The basal surface of satellite cells attaches to the basal lamina and the apical surface to the myofiber. M-cadherin, a well-known satellite cell marker, and its partner b-catenin are localized on the apical surface and form cell-cell adherence junctions with the myofiber (Goel et al, 2017;Irintchev et al, 1994). Pard3, a member of the Par complex, is localized along the apical surface of satellite cells (Dumont et al, 2015b;Troy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by previous work demonstrating aging is associated with a loss of MuSC derived contributions in the vicinity of NMJs, a reduction in post-synaptic myonuclei, and accelerated NMJ degeneration upon MuSC depletion 17 . The attractive interaction between MuSCs and denervation requires further study, but development of filopodia has previously been observed for MuSCs 14,63 and may facilitate transport of signaling ligands 64 or local changes in cadherin signaling 65 that is critical for synaptic patterning 66 .…”
Section: Discussionmentioning
confidence: 99%
“…In mice lacking Notch1 and Notch2 in satellite cells, an inability to maintain quiescence can be observed, resulting in precocious entry into the cell cycle and in the end to a loss of satellite cells [73]. Cross talk of Notch signaling with the vascular niche is also important for regulating satellite cell quiescence-reminiscent of the role of cell adhesion molecules such as Cadherins, which control the transition from quiescence to activation through interaction with the myofiber niche [74,75]. The importance of the interaction of Notch with the niche is further highlighted in a recent study by Baghdadi and colleagues who show that Notch-1/RBPJ controls expression of the extracellular matrix (ECM) molecule Collagen-V [76].…”
Section: Notch Signaling In Satellite Cellsmentioning
confidence: 99%